1991
DOI: 10.1017/s0022050700038341
|View full text |Cite
|
Sign up to set email alerts
|

The Myth of Free-Trade Britain and Fortress France: Tariffs and Trade in the Nineteenth Century

Abstract: This examination of official commercial statistics suggests that the conventional wisdom regarding early free-trade efforts of Britain and France is wrong. French average tariff levels were, surprisingly, consistently below those of Britain throughout most of the nineteenth century, even after the abolition of the Corn Laws and before passage of the 1860 Treaty of Commerce. Previous scholarship has focused on French commercial policies covering a narrow range of items and has largely ignored the overall trade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
12

Year Published

1991
1991
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(50 citation statements)
references
References 5 publications
3
35
0
12
Order By: Relevance
“…In fact, in our sample, some French tariffs, such as the Briare Canal, exhibited the most efficient results even when considering American tariffs. In this finding, we can agree with authors like Nye (1991) and argue that Chevalier was trying to denounce a larger gap than actually existed to accelerate the changes he wished to see in French transportation policy. …”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In fact, in our sample, some French tariffs, such as the Briare Canal, exhibited the most efficient results even when considering American tariffs. In this finding, we can agree with authors like Nye (1991) and argue that Chevalier was trying to denounce a larger gap than actually existed to accelerate the changes he wished to see in French transportation policy. …”
Section: Resultssupporting
confidence: 86%
“…The construction of this palace impressed him deeply, especially its rapidity and the building's design and transparency to light. However, he was mainly impressed by British tariffs, which could be noted as the first signal of his favor of the future Cobden-Chevalier Treaty 5 (although Nye, 1991, confirmed that British tariffs were consistently lower than those of France).…”
Section: A Note On Chevalier's Life and Bibliographymentioning
confidence: 98%
“…Despite the impact of revenue tariffs on average customs duties, many features of Table 1 correspond with what we know about the tariff history of the period, in particular the high United States and low United Kingdom tariffs (although the British index for 1875±9 is slightly higher than that for France, mirroring the debate between Nye (1991) and Irwin (1993)). Even features of Table 1 that seem surprising are often compatible with other evidence on relative protection levels in the late 19th century.…”
Section: Tariffs and Growth: Some Cross-country Evidencementioning
confidence: 81%
“…This result was achieved also thanks to quite high duties on high-demand low-elasticity goods, such as mineral oils, alcohol and tobacco. The trade policy of European countries in the decades before World War I may have resembled more that of Britain in the 1840S-70S (Nye 1991) than the importsubstitution strategies of the LDCs in the 1950S-60S. 17 The ranking for overall protection (Estevadeordal 1997, Table 6) does not tally with the product-level data of Table 7.…”
Section: What Can We Learn From the Italian Case?mentioning
confidence: 99%